The development of a putative microbial product for use in crop production - Gumede, Halalisani (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2008)
The challenges faced by the agricultural sector especially around improving production yields using environmentally friendly solutions have received market attention. Biological intervention can range from application of biological products to enhance the nutritional value of crops or to control plant pathogens. Biostart, a biological product that demonstrated growth enhancement when applied in lettuce crops is currently in the market. The product is comprised of a consortium of bacterial isolates (Bacillus licheniformis, Brevibacillus laterosporus and Bacillus laterosporus) but the contribution of the individual isolates to growth enhancement had not been elucidated. Green house experiments on lettuce seedlings with individual and mixed treatments were commissioned to determine such contribution. There was either no or marginal growth enhancement observed in the experiments. The results showed that the product was effective as a consortium and not as individual isolates. Further isolation and screening for potential Bacilli with antifungal properties was undertaken. An isolate identified as Bacillus subtilis that demonstrated inhibition against a wide spectrum of fungi, and especially the phytopathogenic Verticillium dahliae and Fusarium oxysporum, was successfully identified. The isolate was cryo-preserved and cultivated to significant levels at bench scale. A characterized comparison of different putative products with known systematic fungicide showed potential application even of heat treated products. The product showed control V. dahliae when tested in green houses with potatoes and tomatoes as test crops. This isolate has been targeted for further development as a biological control product.
Keywords: Agricultural productivity; Agriculture -- Economic aspects; Microbial products; Bacterial diseases of plants; Biological pest control agents; Lettuce -- Diseases and pests; Crops -- Nutrition; Bacillus (Bacteria); Phytopathogenic microorganisms -- Control